THE DEVELOPMENT OF EDUCATIONAL PUZZLE GAME BASED ON THE LOCAL WISDOM USING FLASH MEDIA TO EDUCATE THE STUDENTS’ CHARACTERISTIC OF PRIMARY SCHOOL - Herwin Widyatmoko (Universitas Muria Kudus, 2019)
This research aims to development Puzzle Game by using Flash media on theme 4 my obligations and rights for third grade of elementary school dan to describe theeffectiveness of Puzzle Game using Flash media on theme 4 my obligations and rights for third grade of elementary school. The types of this research are Research and Development. This research consists of seven stages; 1) potential and problem; 2) data collection; 3) product design; 4) validation design; 5) revised design; 6) product trial; 7) revised product. The research data is the need for educational Puzzle Game, the prototype of educational Puzzle Game and the effectiveness of educational Puzzle Game. Data collection techniques consist of an observation, interview, questioner and documentation. The data analysis technique uses descriptive analysis. Descriptive data analysis in this study was used to determine the need test for the media and expert validation test, while totest the effectiveness of the media using the t test. Data sources of this research are the students of third grade and teacher of SD N 01 Pulorejo 01, SD N Winong 01, SD N Kebolampang as elementary experimental groups and SD N Sumbermulyo 01, SD N Kropak 02, SD N Godo 03 as elementary school control groups in Winong district, Pati Regency. The results of the puzzle game media prototype are a set of media containing puzzle games using flash applications, manual puzzle games, and puzzle game guidance. The effectiveness test results show that the puzzle media game is effective, which is indicated by the results of the t test. The results of the t test in the experimental and controlgroups were 9.052. Data from t test shows that t count bigger than t table, which is 9.052 bigger than 1.657 then Ho is rejected and Ha is accepted. Based on the t test, it can be concluded that the application of puzzle game media in class III is effective and suitable for use in learning activities